Proteomics in Detection and Monitoring Chronic Lung Diseases: The Human Nasal Epithelium as a Molecular Model - Simões, Tânia (2012)
Asthma and chronic obstructive pulmonary disease (COPD) are major causes of mortality and morbidity worldwide. The current state-of-art diagnosis and management schemes are suboptimal for both diseases as the incidence of asthma has risen by 250% over the last two decades and COPD is estimated to become the third leading cause of death worldwide within the next decade. Additionally, these diseases represent a very important threat to global economies in direct and indirect medical costs and lost working days [1,2]. Asthma is a chronic inflammatory disorder of the airways associated with airway hyperresponsiveness that leads to recurrent episodes of wheezing, breathlessness, chest tightness and coughing. These episodes are usually associated with widespread, but variable, airflow obstruction within the lung [1]. Chronic airflow obstruction is also characteristic of COPD but, in contrast to asthma, is not fully reversible, even under the action of bronchodilators, and is usually progressive. A combination of small airway disease -obstructive bronchiolitis - and parenchymal destruction - emphysema, leads to COPD clinical manifestation [2]. A number of factors influence a person’s risk of developing these lung diseases, which include host factors, primarily genetic, and environmental factors, such as allergens and tobacco smoke in asthma and COPD, respectively